Natural Mineral for Improving Concrete Compressive Strength - Namdar, Abdoullah; Ideris, Zakaria; Pelko, Azam Khodashenas; Nurmunira, Muhammad (Trans Tech Publications Inc., 2014)
Several concrete additives have been innovated for improving concrete quality. In this research work the treated kaolin by heat has been used as concrete additive. Kaolin was subjected to the heat for 1 hour in different degree of temperatures. The crystal structure of Kaolin thermally is modified under heat and microstructure of the hydrated samples has been investigated using FESEM. The main objective is to introduce a cost effective concrete additive. The result is indicated that when kaolin subjected to 800 oC and used in 6% quantity as an additive in concrete mixed design, the concrete compressive strength of 14 days is 40% higher than concrete compressive strength of 28 days which is not used any additive. And if 12% additive is used the concrete compressive strength increased in same level on 7 days. This concrete additive reduces construction cost and time.